INSTITUTIONAL MODEL OF CENDERAWASIH ECOTOURISM MANAGEMENT IN AMAI, TABLASUPA VILLAGE, JAYAPURA REGENCY - Krisson Raunsay, Edoward; Costansah Koirewoa, Dolfina (International Journal of Multidisciplinary Reseach, 2026)
Cenderawasih ecotourism management in Papua represents a strategic approach to conserving endemic species while enhancing local community livelihoods. In Amai, Tablasupa Village, Jayapura Regency, ecotourism development faces challenges related to legal status, cross-sector coordination, community participation, human resource capacity, funding, and program innovation. This study aims to formulate an effective, participatory, and sustainable institutional model for ecotourism management that supports habitat conservation and local economic empowerment. A descriptive qualitative method was employed, using in-depth interviews, participant observation, and document analysis. Data were analyzed thematically to identify key institutional elements, including legal frameworks, stakeholder coordination, community involvement, capacity building, funding mechanisms, transparency, and innovation. The findings indicate that successful ecotourism management depends on formal legal support through village regulations and government policies, strong cross-sector collaboration among government, communities, academics, and the private sector, and active community participation using a pentahelix approach. Strengthening human resource capacity, diversifying funding through partnerships, and integrating research-based environmental education enhance sustainability.